The role of temporal shrub encroachment for the maintenance of Spanish holm oak Quercus ilex dehesas - Ramírez, José Alberto; Díaz, Mario (Forest Ecology and Management, 2008)
Dehesas are man-made systems composed by evergreen oaks (Quercus ilex and Quercus suber) scattered over a grassland understorey. They cover about 3.1 million ha in the southwest of the Iberian Peninsula and are to be preserved under the EU Habitats Directive due to the high levels of plant and animal diversity they maintain. The main current threat to long-term dehesa farming is a chronic absence of natural tree regeneration.We test whether dehesa abandonment would promote natural regeneration, how size structure of tree populations change after abandonment, and whether shrub encroachment would enhance seedling recruitment by measuring the size structure of mature tree populations, shrub cover and seedling density in 17 dehesa farms of known date of abandonment. Size structures were approximately bell-shaped in farms abandoned less than 16 years ago, progressively approaching afterwards the inverse J-shaped distribution typical from holm oak forests. Proportions of young mature trees changed with age of abandonment according to a logistic growth function. Proportions typical from forests (70–80%) were reached 30 years after abandonment, whereas balanced numbers of young and old trees were reached 20–25 years after abandonment. Short-term seedling recruitment was not related to age of abandonment or to covers of most dominant shrubs and was positively related to cover of mature trees and of Cytisus multiflorus, a nurse shrub for holm oak seedlings. Synthesis and applications: Conservation of dehesas and their associated biodiversity values should be based on financing temporal abandonment of productive dehesa farming for 20 years, keeping land in good agricultural condition by re-opening the encroached plots after tree recruitment (i.e. rotational set-aside). The proposed measure has the additional advantages of easy monitoring and straightforward evaluation of its effectiveness.
Keywords: Dehesa; Quercus ilex; Regeneration; rotational set-aside; Shrub cover; Sustainability

The role of temporal shrub encroachment for the maintenance of Spanish holm oak Quercus ilex dehesas - Ramírez, José Alberto; Díaz, Mario (Forest Ecology and Management, 2008)
Dehesas are man-made systems composed by evergreen oaks (Quercus ilex and Quercus suber) scattered over a grassland understorey. They cover about 3.1 million ha in the southwest of the Iberian Peninsula and are to be preserved under the EU Habitats Directive due to the high levels of plant and animal diversity they maintain. The main current threat to long-term dehesa farming is a chronic absence of natural tree regeneration.We test whether dehesa abandonment would promote natural regeneration, how size structure of tree populations change after abandonment, and whether shrub encroachment would enhance seedling recruitment by measuring the size structure of mature tree populations, shrub cover and seedling density in 17 dehesa farms of known date of abandonment. Size structures were approximately bell-shaped in farms abandoned less than 16 years ago, progressively approaching afterwards the inverse J-shaped distribution typical from holm oak forests. Proportions of young mature trees changed with age of abandonment according to a logistic growth function. Proportions typical from forests (70–80%) were reached 30 years after abandonment, whereas balanced numbers of young and old trees were reached 20–25 years after abandonment. Short-term seedling recruitment was not related to age of abandonment or to covers of most dominant shrubs and was positively related to cover of mature trees and of Cytisus multiflorus, a nurse shrub for holm oak seedlings. Synthesis and applications: Conservation of dehesas and their associated biodiversity values should be based on financing temporal abandonment of productive dehesa farming for 20 years, keeping land in good agricultural condition by re-opening the encroached plots after tree recruitment (i.e. rotational set-aside). The proposed measure has the additional advantages of easy monitoring and straightforward evaluation of its effectiveness.
Keywords: Dehesa; Quercus ilex; Regeneration; rotational set-aside; Shrub cover; Sustainability